Formation of professional competence for future social educators based on an integrated approach - Utegenova, Meruyert; Sholpankulova, Gulnar; Shavaliyeva, Zulfiya; Zhmailo, Tatyana; Yerepbayev, Nurlan (Journal of Education and e-Learning Research, 2023)
The objective of this study is to assess the efficacy of a comprehensive strategy for developing the professional abilities of social educators. Additionally, it seeks to identify the problems encountered by high schools in this regard and examine the process of cultivating professional competencies. The research comprised a sample of 253 individuals from L. Gumilyov Eurasian National University, located in Astana, Kazakhsta. The study compares the diagnostic results on a quantitative and qualitative level. The assessment standards of Fisher and the descriptive statistics were acquired. The study’s data was gathered by requesting questions from teachers and students, testing, interviews, and evaluations from experts who fit this profile. The findings indicated that future social educators will have problems with their lack of high-level professional competence. Additionally, the majority of employers have requirements that are related to how well students develop their skills as well as their motivation to engage in extracurricular activities, work on themselves, and engage in future professional endeavors. The study revealed that employing an integrated strategy for the training of prospective social teachers yielded the most significant impact on the development of their professional abilities. The study’s findings can be used to improve vocational training for social educators.